Immune-related cardiovascular toxicities of PD-1/PD-L1 inhibitors in solid tumors: an updated systematic review and meta-analysis - Zhang, Chi; Wei, Fengtao; Ma, Wenhan; Zhang, Jingbo (Frontiers in Immunology, 2024)
ABSTRACT Purpose: The objective of this study was to investigate the risk of cardiovascular toxicities related to PD-1/PD-L1 inhibitors in solid tumors. Methods: A literature search was performed following the participants, interventions, comparisons, outcomes, and study design (PICOS) principles, and the study adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data analysis was conducted using Review Manager version 5.4. Results: This meta-analysis included 69 randomized controlled trials (RCTs) divided into five groups based on the treatment regimens: PD-1/PD-L1 + chemotherapy versus chemotherapy, PD-1/PD-L1 versus chemotherapy, PD-1/PD-L1 versus placebo, PD-1/PD-L1 + CTLA-4 versus PD-1/PD-L1 and PD-1/PD-L1 + CTLA-4 versus chemotherapy. Compared to chemotherapy treatment alone, PD-1/PD-L1 +chemotherapy significantly increased the risk of hypertension [all-grade (OR = 1.27, 95% CI [1.05, 1.53], p = 0.01); grade 3–5 (OR = 1.36, 95 % CI [1.04, 1.79], p = 0.03)], hypotension [all-grade (OR = 2.03, 95 % CI [1.19, 3.45], p = 0.009); grade 3–5 (OR = 3.60, 95 % CI [1.22, 10.60], p = 0.02)], arrhythmia [all-grade (OR = 1.53, 95 % CI [1.02, 2.30], p = 0.04); grade 3–5 (OR = 2.91, 95 % CI [1.33, 6.39], p = 0.008)] and myocarditis [all-grade (OR = 2.42, 95 % CI [1.06, 5.54], p = 0.04)]. The risk of all-grade hypotension (OR = 2.87, 95 % CI [1.26, 6.55], p = 0.01) and all-grade arrhythmia (OR = 2.03, 95 % CI [1.13, 3.64], p = 0.02) significantly increased when treated with PD-1/PD-L1 inhibitors compared to the placebo. The risks of cardiovascular toxicities are significantly higher with PD-1+CTLA-4 compared to PD-1 alone (OR = 2.02, 95% CI [1.12, 3.66], p = 0.02 ). Conclusion: PD-1/PD-L1 inhibitor leads to an increased risk of cardiovascular toxicities, especially hypertension, hypotension, arrhythmia, and myocarditis.